(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This thesis aims to investigate the neurological outcomes in school-age children following surgical procedures performed under total anesthesia, with a focus on comparing the effects of short-duration versus long-duration surgeries. The key objectives are: To assess the incidence of new-onset neurological deficits, such as motor, sensory, and cognitive impairments, in children after undergoing short-duration (less than 4 hours) versus long-duration (4 hours or more) surgical interventions.